2015
DOI: 10.1038/onc.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiological and synthetic IAP antagonism on c-IAP-dependent signaling

Abstract: Cellular inhibitor of apoptosis proteins 1 and 2 (c-IAP1/2) play central roles in signal transduction mediated by numerous receptors that participate in inflammatory and immune responses. In certain pathways, such as activation of NF-κB, their degradation is a major regulatory event and is physiologically induced by activation of receptors. Additionally, a number of synthetic compounds have been developed that also target the c-IAPs and induce their degradation. However, the extent of a synthetic IAP antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Another crucial point for increasing cell susceptibility to TRAIL is inhibition of the anti-apoptotic protein. Previous studies supported that TRAIL-resistant cells were re-sensitized by Bcl-2 or IAP antagonist (17,18). Here we revealed that PTX itself markedly inhibited expression of C-IAP1, C-IAP2, Livin and Mcl-1 in both SGC-7901 and MGC-803 cells, and combined application of PTX and TRAIL exhibited similar effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another crucial point for increasing cell susceptibility to TRAIL is inhibition of the anti-apoptotic protein. Previous studies supported that TRAIL-resistant cells were re-sensitized by Bcl-2 or IAP antagonist (17,18). Here we revealed that PTX itself markedly inhibited expression of C-IAP1, C-IAP2, Livin and Mcl-1 in both SGC-7901 and MGC-803 cells, and combined application of PTX and TRAIL exhibited similar effects.…”
Section: Discussionsupporting
confidence: 82%
“…The most basic cause is dysfunction of death receptors due to hyper-methylation (11), mutation (12) and loss of cell surface expression (13). The defects in caspase protein (14) and overexpression of prosurvival proteins, such as IAP family and anti-apoptotic Bcl-2 family members (15)(16)(17)(18), are also linked to TRAIL sensitivity. In addition, more recent findings suggested that cell survival signals, including mitogen-activated protein kinase (MAPK) pathway, phosphatidylinositol 3-kinase/Akt pathway, and transcription factor NF-κB played pivotal roles in regulation of TRAIL signaling (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-8, an important factor in apoptosis, has been implicated in the regulation of inflammation in an apoptosis-independent manner [82][83][84], and has been shown to participate in the differentiation of monocytes into macrophages through regulation of NF-jB via cleavage of RIP1 [85,86]. Additionally, we found that gene expression regulated by c-IAP degradation was dependent on caspases, illustrating another non-apoptosis-related function for these proteins [70]. These data may broaden the functional scope of the IAP/caspase interaction beyond regulation of cell death, with the IAPs acting as general regulators of caspase activity.…”
Section: Iaps and Smac Mimeticssupporting
confidence: 53%
“…; Kocab et al . ). In lamina II neurons obtained from morphine‐treated rats, pre‐treatment with SP600125 (40 μM for 1 h) significantly reduced the frequency (4.40 ± 0.44 Hz vs. 6.45 ± 0.60 Hz), but not the amplitude, of mEPSCs ( n = 10 neurons, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…JNK2 is expressed pre-synaptically and plays a role in NMDAR-mediated glutamate release in the cortex (Nistico et al 2015). SP600125 is an anthrapyrazolone capable of inhibiting JNK1, JNK2, and JNK3 with high affinity Kocab et al 2015). In lamina II neurons obtained from morphine-treated rats, pretreatment with SP600125 (40 lM for 1 h) significantly reduced the frequency (4.40 AE 0.44 Hz vs. 6.45 AE 0.60 Hz), but not the amplitude, of mEPSCs (n = 10 neurons, Fig.…”
Section: Jnk Participates In Morphine-induced Increases In Pre-synaptmentioning
confidence: 99%